Peran Etika Egoisme Sebagai Pemoderasi Pengaruh Keefektifan Pengendalian Internal dan Profesionalisme Auditor Internal Terhadap Pengungkapan Fraud - Riyas Tuti; Susi Dwi Mulyani (Faculty of Economic and Business, 2021)
Fraud disclosure is needed for companies to avoid actions that can harm the company. This study aims to analyze the effect of internal control effectiveness and internal auditor professionalism on fraud disclosure by using a moderating variable, namely ethics-egoism. The data had been obtained from the perceptions of accounting students from the Faculty of Economics and Business, Trisakti University. The sample had been obtained by purposive sampling method is 114 respondents. The results show that the internal control effectiveness has a positive effect on fraud disclosure, while the internal auditor professionalism has no effect on fraud. The results of this study also prove that ethics of selfishness as a moderating variable is able to weaken the effect of the internal control effectiveness on fraud disclosure, but is not able to weaken the effect of internal auditor professionalism auditors on fraud disclosure.